Penerapan Enkripsi Menggunakan Metode Elgamal guna Meningkatkan Keamanan Data - Fahri Husaini; Akim M.H Pardede; Imeldawaty Gultom (Yayasan Kita Menulis, 2022)
Data security is very important in maintaining the confidentiality of information, especially those containing sensitive information whose contents should only be known by the entitled people. especially if the transmission is done through a public network, if the data is not secured beforehand, it will be very easy to be intercepted and the contents of the information known by irresponsible people. One of the methods used to secure data is to use a cryptographic system, namely by providing the information content (plaintext) into content that is not understood through the encryption process, and to retrieve the original information, a description process is carried out, accompanied by using the correct key. Therefore, the author recommends the Elgamal algorithm to be able to provide security for text data. The reason the author uses the ElGamal algorithm is that the ElGamal algorithm is part of asymmetric cryptography where the formation of one of the keys uses prime numbers and focuses on the strength of the key in solving discrete logarithm problems.